Epistaxis etiology and treatment - Kożuchowski, Marcin; Prylińska, Monika (Journal of Education, Health and Sport, 2021)
Epistaxis occurs in approximately 60% of the general population. Every tenth person requires treatment in a hospital setting. Epistaxis occurs in all age groups, reaching its peak in children around 10 years of age and in adults around 80 years of age. The frequency and intensity of epistaxis are anatomically based on numerous vascular connections. The cause of epistaxis in most cases can be determined on the basis of a detailed history and physical examination. There are a number of treatments available for nose bleeds. From widely available methods such as nasal tamponade to more advanced endovascular procedures.